Challenges and opportunities using online portals to recruit diverse patients to behavioral trials. (18th September 2019) - Tabriz, Amir Alishahi; Fleming, Patrice Jordan; Shin, Yongyun; Resnicow, Ken; Jones, Resa M; Flocke, Susan A; Shires, Deirdre A; Hawley, Sarah T; Willens, David; Lafata, Jennifer Elston
Abstract: We describe the use of an online patient portal to recruit and enroll primary care patients in a randomized trial testing the effectiveness of a colorectal cancer (CRC) screening decision support program. We use multiple logistic regression to identify patient characteristics associated with trial recruitment, enrollment, and engagement. We found that compared to Whites, Blacks had lower odds of viewing the portal message (OR = 0.46, 95% CI = 0.37–0.57), opening the attached link containing the study material (OR = 0.75, 95% CI = 0.62–0.92), and consenting to participate in the trial (OR = 0.85, 95% CI = 0.67–0.93). We also found that compared to Whites, Asians had lower odds of viewing the portal message (OR = 0.53, 95% CI = 0.33–0.64), opening the attached link containing the study material (OR = 0.76, 95% CI = 0.54–0.97), consenting to participate in the trial (OR = 0.68, 95% CI = 0.53–0.95), and completing the trial's baseline questionnaire (OR = 0.59, 95% CI = 0.36–0.90). While portals offer an opportunity to mitigate human bias in trial invitations, because of racial disparities—not only in who has a portal account, but in how they interact with trial recruitment and enrollment material within the portal—using portals alone for trial recruitment may generate study samples that are not racially diverse.